Optical Temperature Sensor based on Sagnac Interferometer - Omar, Mohd Azwadi; Cholan, Noran Azizan; Mohd, Aminuddin; Azhan, Mirsa Nurfarhan Mohd; Talib, Rahmat; Ngajikin, Nor Hafizah (International Journal of Engineering and Technology, 2018)
Optical temperature sensors gain interest from the community recently due to their immunity to electromagnetic interference and ruggedness against chemical and mechanical disturbances as opposed to the conventional temperature sensors such as thermocouples and resistance temperature detectors. Optical temperature sensors come with many varieties and Sagnac interferometer is one of them. In this work, an all-fiber temperature sensor is proposed and experimentally demonstrated. The proposed optical temperature utilizes Sagnac interferometer as the temperature head. The underlying mechanism for this sensor is based on the temperature dependence of a polarization maintaining fiber (PMF) in the Sagnac interferometer. The PMF birefringence which is influenced by temperature affects the phase difference of two incoming lights that enter the Sagnac interferometer and this contributes to the shifting of the transmission spectrum. The input light for the sensor characterization is provided by a custom-made amplified spontaneous emission source which comprises of a tunable laser source, a 980 nm laser diode pump, a wavelength division multiplexing coupler and a 10 m long erbium-doped fiber. Experimental results indicate that the temperature does affect the PMF characteristic.Â As the temperature increases from 30Â°C to 45Â°C, the wavelength dip reduced from 1553.8 nm to 1536.78nm. This proposed optical temperature sensor has a sensitivity of-1.0345 nm/Â°C. The development of this optical temperature sensor is promising especially for the measurement in the harsh environment.